2012
DOI: 10.5267/j.msl.2012.05.015
|View full text |Cite
|
Sign up to set email alerts
|

An empirical study on the effects of human resource supporting strategies on job satisfaction

Abstract: One of the essential functions of human resource management is to take care of skilled employees. The process is normally divided into two categories: first category includes different activities such as having health and safety in working centers, performing healthy and sport programs and some other similar activities to save and improve employees' physical characteristics. The second group includes other important issues normally called benefit packages, which includes good health insurance and retiring plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…Khodaei Valahzaghard et al (2012) performed another investigation to study the effects of human resource supporting strategies on job satisfaction. In their study, the effects of related services to support employee to reach job satisfaction and employee activities in one of Iranian banks called Mellat bank was investigated using 276 random samples.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Khodaei Valahzaghard et al (2012) performed another investigation to study the effects of human resource supporting strategies on job satisfaction. In their study, the effects of related services to support employee to reach job satisfaction and employee activities in one of Iranian banks called Mellat bank was investigated using 276 random samples.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The other findings of this survey was that stress posed from management team had different effects on employees with different marital status but there were no meaningful differences between married and single couples in terms of other factors posing stress such as unsuitable working conditions, fear of job stability or difficulty of job conditions. According to Khodaei Valahzaghard et al (2012), one of the necessary functions of human resource management is to take care of skilled employees. The process can be divided into two categories: first category includes various activities such as having health and safety in working centers, performing healthy and sport programs and some other similar activities to save and improve employees' physical characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Khodaei Valahzaghard et al (2012) explained that one of the essential functions of human resource management is to take care of skilled employees. The process is classified into two categories.…”
Section: Introductionmentioning
confidence: 99%
“…Whenever a firm provides good benefit package and supporting programs, there is a better chance for job satisfaction among employee. Khodaei Valahzaghard et al (2012) considered the impacts of related services to support employee to reach job satisfaction and employee activities in one of Iranian banks called Mellat bank is investigated using 276 random samples. The results demonstrated that employees were relatively satisfied from the benefit package of the bank and they were relatively happy on working for such organization.…”
Section: Introductionmentioning
confidence: 99%